Tingkat Pertumbuhan dan Produksi Kelapa Sawit (Elaeis guineensis Jacq.) pada Berbagai Topografi Lahan - Kafrawi, K; Hesti, Nur; Syatrawati, S; Rahim, Iradhatullah; Kumalawati, Zahraeni (Fakultas Pertanian, Peternakan dan Perikanan Universitas Muhammadiyah Parepare, 2023)
This study aims to compare oil palm growth and yield in various topography on one stretch of land. Topography can affect the rate of erosion on agricultural land. High erosion rates transport nutrients to lower places, reducing land productivity, including oil palm plantations. It conducted the research by taking data on the growth and production of palm oil at PT. Perkebunan Nusantara XIV Keera-Maroangin Unit in October - December 2020. Observations were made of oil palm plantations on 3 types of land topography, namely (1) flat land: slope <3%, with a height difference <2 m, (2) undulating land: slope 8-15%, with a height difference of 10-50 cm, and (3) hilly land: slope 15-30%, with a height difference of 50-300 cm. Available secondary data is data from samples taken using a systematic random method. The sample data was then statistically processed using the two-party test method at the 0.05 level. The results showed that all growth parameters, namely plant height (98.09 cm), trunk circumference (301.94), frond length (413.94 cm) and bunch weight production (6.76 kg) of oil palm were found to be better on land with flat topography than other types of topography, while undulating land is better than sloping land, except for the parameter of frond length, oil palm growth and production are better than sloping land.